Penerapan Teknologi Sistem Informasi dalam Proses Pembuatan Surat Keterangan Kematian Berbasis Elektronik Menggunakan Metode Agile - Fuad Satrio Nugraha; Syahidin, Yuda; Suryani, Ade Irma (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Researchers conducted research aimed at creating an electronic-based death certificate information system application to manage patient death data accurately to increase work effectiveness and efficiency in medical records installations so that the source of relevant death report data is available. One of the problems found was providing information on patient death certificates at Kebonjati Hospital which was felt to be less efficient because it still used manual methods and handwritten media in the form of photocopy paper, which reduced the quality of medical records and resulted in them being inaccurate because the writing was not clear and blurry. In conducting this research, the author conducted research usingl qualitative researchl using al descriptive approachl including data collection, lobservation, and linterviews. The system development method uses agile methodology. The results of implementing the death certificate reporting system are designed using Visuall Studio 2012l and a Microsoftl Access databasel which isl expected to speed up and expedite the work of medical record officers in filling in patient identity, displaying time of death, and obtaining accurate and competent reports.